faktor-faktor yang berhubungan dengan kejadian luka perineum pada ibu nifas di wilayah kerja puskesmas basuki rahmat kota bengkulu tahun 2024 - Wijayanti, Viki (Poltekkes Kemenkes Bengkulu, 2024)
Perineal rips occur in almost 2.7 million incidents worldwide in maternity women, and in 2019, the World Health Organization (WHO) reports that nearly 90% of normal deliveries have perineal rupture, either spontaneously or by episiotomy. Perineal tears are wounds that occur when the baby's birth canal is torn, either spontaneously or due to actions or tools used during labor. Information from the 2023 Bengkulu City Health Office Profile showed 6,553 (93.4%) postpartum mothers. Puskesmas Basuki Rahmat had the highest number of postpartum women at 563 (80.5%), with 122 (54%) postpartum women experiencing perineal wounds, compared to the other 19 health centers in Bengkulu City, the number of postpartum women who experienced perineal wounds was lower. The study's objective, as stated above, was to determine the factors associated with the incidence of perineal wounds in postpartum women in the Puskesmas Basuki Rahmat Working Area in Bengkulu City in 2024. The cross-sectional study comprised 100 postpartum moms with perineal lesions in the Bengkulu City work area of the Basuki Rahmat Health Center. Chi-square statistical data were utilized. The most significant factor influencing postpartum women's continued wound healing is the parity variable (B = 6.367).